2005
DOI: 10.1111/j.0022-2445.2005.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Family and child characteristics linking neighborhood context and child externalizing behavior

Abstract: Neighborhood conditions are related to children's externalizing behavior, although few processes that help explain this association have been identified. With data from 189 primarily low-income Anglo and Mexican American families, we tested a stress process model that included 3 potential mediators of this relationship. The results showed that child stressful life events, association with deviant peers, and parent-child conflict mediated the relationship between neighborhood context and child externalizing beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 48 publications
(47 reference statements)
2
85
1
2
Order By: Relevance
“…Several studies have examined the implications of neighborhood-level prevention and intervention efforts (Aneshensel and Sucoff-McNeely, 2003;Caughy et al, 1999;Roosa et al, 2005). Most research of this type has focused on the role of poverty as a risk factor for negative outcomes, and many neighborhood-informed intervention efforts have focused on relieving the negative effects of poverty (e.g., fostering community and social ties, attempts to reduce crime through watch programs).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the implications of neighborhood-level prevention and intervention efforts (Aneshensel and Sucoff-McNeely, 2003;Caughy et al, 1999;Roosa et al, 2005). Most research of this type has focused on the role of poverty as a risk factor for negative outcomes, and many neighborhood-informed intervention efforts have focused on relieving the negative effects of poverty (e.g., fostering community and social ties, attempts to reduce crime through watch programs).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by previous research, family processes and management are contingent on the larger neighbourhood context (Beyers, Bates, Pettit, & Dodge, 2003;Wu, Palinkas, & He, 2011). Family characteristics may be the intermediate that link neighbourhood context to child internalising and externalising behaviours (Roosa et al, 2005;Wu et al, 2010). It has been found in previous research that youth living in poor neighbourhoods with a higher crime rate tend to receive less social support and supervision from parents than those who live in safer and more resourceful neighbourhoods (Klebanov et al, 1994).…”
Section: Discussionmentioning
confidence: 86%
“…Association with deviant peers is a robust risk factor for child internalizing and externalizing problems, school failure, and drug use, and mediates relations between neighborhood characteristics, stressful events, and child outcomes (e.g., Barrera et al 2002;Cantillon 2006;Roosa et al 2005). Moreover, Dubow et al (1997) found that peer support predicted higher levels of antisocial behavior and drug use in a sample of inner-city neighborhoods in a small metropolitan area and strengthened (rather than attenuated) the link between neighborhood disadvantage and negative child outcome.…”
Section: Child Monitoring and The Regulation Of Children's Peer Groupsmentioning
confidence: 99%